Strategi Pemasaran Inovatif Dalam UMKM - Muhammad Lutfy Adly; Muhammad Irwan Padli Nasution (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The aim of this research is to investigate and analyze innovative ways of marketing applied in small and medium scale businesses. This research uses qualitative research methods by relying on literature studies as a data source. The results of this research identify various innovative marketing strategies that are effective in increasing the competitiveness and sustainability of small and medium businesses. Some of the strategies found include the use of information and communication technology, creativity in developing products and services, and collaboration with external parties. This research also highlights the importance of a deep understanding of markets and customers, as well as the ability to adapt to changes in the business env.ironment to digital business or online sales. These findings provide valuable insights for SME owners and marketing practitioners in formulating relevant and innovative strategies. In addition, this research also illustrates the challenges that SMEs may face in adopting innovative marketing strategies. In conclusion, innovative marketing is a key element in SME business success, and this research makes an important contribution to understanding the critical aspects of implementing it. Keywords: strategy, marketing, innovative Abstrak Tujuan dari penelitian ini adalah untuk menyelidiki dan menganalisis cara-cara inovatif dalam pemasaran yang diterapkan dalam bisnis skala kecil dan menengah. Penelitian ini menggunakan metode penelitian kualitatif dengan mengandalkan studi literatur sebagai sumber data. Hasil penelitian ini mengidentifikasi beragam strategi pemasaran inovatif yang efektif dalam meningkatkan daya saing dan kelangsungan usaha kecil menengah. Beberapa strategi yang ditemukan mencakup penggunaan teknologi informasi dan komunikasi, kreativitas dalam mengembangkan produk dan layanan, serta kerja sama dengan pihak luar. Penelitian ini juga menyoroti pentingnya pemahaman yang mendalam tentang pasar dan pelanggan, serta kemampuan beradaptasi dengan perubahan lingkungan bisnis menjadi bisnis digital atau penjualan berbasis online. Temuan ini memberikan pandangan berharga bagi pemilik UKM dan praktisi pemasaran dalam merumuskan strategi yang relevan dan inovatif. Selain itu, penelitian ini juga menggambarkan tantangan yang mungkin dihadapi UKM dalam mengadopsi strategi pemasaran inovatif. Kesimpulannya, pemasaran inovatif adalah elemen kunci dalam kesuksesan bisnis UKM, dan penelitian ini memberikan kontribusi penting dalam pemahaman aspek-aspek kritis dalam menerapkannya. Kata kunci: strategi, pemasaran, inovatif.